Multi-criteria and multi-objective evaluation to optimize the selection of areas to establish forest plantations - Hernández-Zaragoza, Pedro; Valdez-Lazalde, José René; Aldrete, Arnulfo; Martínez-Trinidad, Tomás (Instituto de Ecología, A.C., 2019)
Selecting where to establish forest plantations is crucial to maximize its probability of success. Multi-criteria decision analysis for land suitability accomplishes this purpose by matching ecological requirements of chosen species for planting against soil productive potential and climate conditions. This study describes a model developed under both a hierarchical analytical process framework and a multi-objective land allocation approach, in a GIS environment, to select optimal sites for establishing six pine species (Pinus engelmannii, P. leiophylla, P. arizonica, P. cembroides, P.chihuahuana and P. durangensis) for commercial purposes in Northern Mexico. The model considers climatic, edaphological and topographical criteria and subcriteria that affect the location of suitable areas to establish commercial forest plantations. Sub-criteria values were standardized, weighted and ordered by pairwise matrices considering their importance regarding to planting such tree species. Initially, the model quantified the suitability of the land to establish forest plantations. Then, such suitability results were optimized through a multiobjective procedure to identify the best species to plant in the area under four decision scenarios: harvesting age, wood quality, survival, and susceptibility to both pests and diseases. The results indicate that the municipality of Durango has the greatest number of optimal areas to establish forest plantations with the species analyzed.